Aerobic but not Resistance Exercise Can Induce Inflammatory Pathways via Toll-Like 2 and 4: a Systematic Review - Paula Andréa Malveira Cavalcante; Marcos Fernandes Gregnani; Jessica Salles Henrique; Fábio Henrique Ornellas; Ronaldo Carvalho Araújo (SpringerOpen, 2017)
Abstract Background Only a few studies have addressed the relationship between toll-like receptors 2 and 4 (TLR2 and TLR4) and the production of local and systemic cytokines in response to physical exercise, and they have produced conflicting results. We aimed to determine whether acute and chronic exercise outcomes are associated with changes in TLR2 and TLR4 expression and signaling and if so, the mechanisms that connect them. Methods PubMed database were consulted. This systematic review selected 39 articles, 26 involving humans and 13 based on rodents. Results In acute resistance exercise studies, 75% reported a decrease in TLR4 or TLR2 expression and 25% did not find differences. For chronic resistance exercise studies, 67% reported a reduction of expression and 33% did not find differences. Studies of both types reported reductions in pro-inflammatory cytokines. In acute aerobic exercise studies, 40% revealed a decline in the expression of the receptors, 7% reported no significant difference, 40% showed an increase, and 13% did not evaluate their expression. Fifty-eight percent of studies of chronic aerobic exercise revealed a reduction in expression, 17% did not find a difference, and 25% reported increases; they also suggested that the expression of the receptors might be correlated with that of inflammatory cytokines. In studies on combined exercise, 50% reported a decline in receptors expression and 50% did not find a difference. Conclusions The majority of the articles (54%) link different types of exercise to a decline in TLR4 and TLR2 expression. However, aerobic exercise may induce inflammations through its influence on these receptor pathways. Higher levels of inflammation were seen in acute sessions (40%) than regular sessions (25%).